STRATEGI PENGELOLAAN PENGGUNAAN GADGET DI KELAS UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI ERA DIGITAL (STUDI PADA SISWA SMK YASTI CISAAT KABUPATEN SUKABUMI) - Ari Maulana Ibrahim; Donita Indriani; Efni Shofiyah; Felicia Marsha Nurfauziah; Kholiludin Mahalli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze strategies for managing gadget use in the classroom to enhance students' learning interest in the digital era. The study used a qualitative approach with a case study method at SMK Yasti Cisaat, Sukabumi Regency, with 34 students as subjects. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results indicate that purposeful gadget use can enhance students' learning interest. Effective strategies include establishing rules for gadget use, utilizing learning applications, active teacher supervision, and integrating gadgets into the learning process. Implementing these strategies can increase student participation, attention, and learning independence. However, unmanaged gadget use can cause distraction and reduce learning focus. Therefore, teachers need to actively manage gadget use to ensure optimal use in learning.